2014
DOI: 10.1016/j.ecss.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and fate of urban particles in coastal waters: Settling rate, size distribution and metals contamination characterization

Abstract: The evaluation of contaminant net fluxes from the coast to the open sea requires the study of terrigeneous particles behaviour and fate. We studied the particles issued from two small coastal rivers whose waters are mixed with treated wastewater (TWW) coming from the Marseille wastewater treatment plant (WWTP) just before discharge to the Mediterranean Sea. An experimental device was developed and used to investigate particles settling rates, size distribution and metallic contamination when mixing with seawat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 61 publications
2
31
0
1
Order By: Relevance
“…For example, while very high variability was measured for cadmium (Cd) for the first four deployment periods at sites SP1 and SP3, relatively low variability was found for the same period at site SP2. Such specific variability patterns clearly show the overall dynamics of trace metal concentrations at the study area, but also demonstrates that the discrete sampling methodology, most widely used in environmental monitoring programs and research studies, [2,3,37,38] is not ideal for (highly) dynamic aquatic systems. [39][40][41] Examining the entire 5-month period, specific trends of trace metal concentrations varied by metals and sites.…”
Section: Spatio-temporal Distribution Of Dissolved Trace Metalsmentioning
confidence: 99%
“…For example, while very high variability was measured for cadmium (Cd) for the first four deployment periods at sites SP1 and SP3, relatively low variability was found for the same period at site SP2. Such specific variability patterns clearly show the overall dynamics of trace metal concentrations at the study area, but also demonstrates that the discrete sampling methodology, most widely used in environmental monitoring programs and research studies, [2,3,37,38] is not ideal for (highly) dynamic aquatic systems. [39][40][41] Examining the entire 5-month period, specific trends of trace metal concentrations varied by metals and sites.…”
Section: Spatio-temporal Distribution Of Dissolved Trace Metalsmentioning
confidence: 99%
“…There is a linear correlation between heavy metal concentration and the fraction of particles, i.e., metals increased with decreasing grain size of sediments [1]. A study conducted in coastal waters of Marseille found higher concentrations of heavy metals in the finest fraction of sediments [5]. The accumulation of heavy metals in sediments also depends on hydrographic conditions such as temperature, salinity, pH and DO.…”
Section: Introductionmentioning
confidence: 99%
“…) of each fraction was governed by Stokes' law (Mantovanelli and Ridd, 2006), and the particle diameter (Ø; in m) for a given settling velocity was calculated according to Oursel et al (2014) for diameters varying from N276 to b 0.78 μm. Prior to the analysis, a small portion (10%) of the collected samples was filtered through 25-mm glass filters (Whatman GFF, 0.7 μm) for particulate organic carbon (POC) analysis.…”
Section: Settling Rate Experimentsmentioning
confidence: 99%
“…A simple experimental device proposed by Oursel et al (2014) was setup using two identical vertical Plexiglas tubes (1 m length and 10 cm diameter), open on the top and equipped with a valve at the bottom to collect water samples. The tube was filled with 7 L of coastal seawater sampled 2 km offshore and at a 4-m depth and then acclimatised for 1 day to obtain a homogeneous temperature of the water column (close to 20°C).…”
Section: Settling Rate Experimentsmentioning
confidence: 99%
See 1 more Smart Citation